Óxidos de TiO2 dopados com Nb: Síntese e aplicação em células fotovoltaicas de terceira geração - TRACTZ, GIDEÃ TAQUES (2022)
Photovoltaic systems are promissing devices to supply the growing energy demand, aiming to the use of clean energy. Third generation of solar systems have a semiconductor oxide and an electron-donor material in the composition. These, when incident by sunlight might generate excitons which are transported to device interfases, generating a current flow. As an alternative to potentiate these systems, a mixture of oxides is used, which has been able to influence the cell parameters. Thus, this thesis aims to synthesize TiO2 and TiO2,Nb and apply it as a electron transport layer in third generation of solar devices. The synthezed materals were characterized by X-ray diffraction, infrared spectroscopy, UV-vis spectroscospy, scanning electron microscopy, X - ray excited photoelectron spectroscopy, and dynamic light scattering. Then, the oxides were applied in a dye-sensitized solar cell and in a hybrid cell, which was characterized by: j-E curves, photochronoamperometry, electrochemical impedance spectroscopy, photocurrent and Intensity modulated photovoltage and photocurrent spectroscopy and via measurements by Mott-Schottky. The results showed that the oxides produced from TiO2 + 5% Niobium (w/w) showed superior results when applied as an electron transport layer, achieving a photoconversion energy efficiency of ɳ = 6.49% (jsc =10,065 mA cm-2; Voc= 0,821V; FF = 0,471 at Pe = 60 mW cm-2) after a morphological processing. Furthermore, it was found that such potentiation is due to the creation of new states below the TiO2 conduction band, arising from the doping of Niobium in the majority oxide matrix.